The need for fission-track data transparency and sharing - M. T. Tamer; M. T. Tamer; L. Chung; R. A. Ketcham; A. J. W. Gleadow (Geochronology)
We report a new image-based inter-analyst study to investigate apatite fission-track grain selection and analysis by 13 participants from an image dataset that included grains of variable quality. Results suggest that participants with less experience selected a higher percentage of unsuitable grains, while participants from the same laboratories generally provided similar results. Less analytical experience may result in the rejection of suitable grains or the inclusion of unsuitable ones. While inappropriate omission and inclusion can both bias results, the latter is more pernicious due to the standard practice of achieving a pre-decided number of analyses; particularly in difficult samples, there is a danger of “compromising data quality” and integrity by weakening selection criteria. Juxtaposing selected regions of interest (ROIs) on the same grains indicates that zoned grains and grains with inclusions and defects yield varying track density estimates, indicating that ROI placement can be an influential factor. We hereby propose the development of image data repositories for the purpose of achieving global data transparency. In this repository, images and analyses can be accessed, reviewed, and reanalyzed. In addition, we propose the implementation of global guidance for fission-track analysis, digital teaching modules, and open science. We also point out the need for new approaches to zeta calibration that include consideration of grain quality, methods of uranium determination, and etching protocols.